Interleukin-1 and Systemic Sclerosis: Getting to the Heart of Cardiac Involvement - De Luca, Giacomo; Cavalli, Giulio; Campochiaro, Corrado; Bruni, Cosimo; Tomelleri, Alessandro; Dagna, Lorenzo; Matucci-Cerinic, Marco (Frontiers in Immunology, 2021)
Systemic sclerosis (SSc) is rare and life-threatening connective tissue disease characterized by diffuse vascular damage, aberrant activation of the immune system, inflammation and fibrosis of skin and internal organs, including the heart. Cardiac involvement is frequent in SSc patients, even though often asymptomatic at early stages, and represents one of the major causes of SSc-related mortality. Heart involvement has a variable clinical presentation, and its pathogenesis is not completely understood. Myocardial fibrosis is historically considered the immunopathologic hallmark of SSc heart disease. This unique histological feature is paralleled by distinctive clinical and prognostic features. The so-called “vascular hypothesis” represents the most credited hypothesis to explain myocardial fibrosis. More recently, the prominent role of an inflammatory myocardial process has been identified as a cardinal event in the evolution to fibrosis, thus also delineating an “inflammation-driven pathway to fibrosis”. The pro-inflammatory cytokine interleukin(IL)-1 has an apical and cardinal role in the myocardial inflammatory cascade and in cardiac dysfunction. The primary aim of this perspective article is: to present the emerging evidence on the role of IL-1 and inflammasome in both SSc and heart inflammation, to review the complex interplay between cellular metabolism and inflammasome activation, and to discuss the rationale for targeted inhibition of IL-1 for the treatment of SSc-heart involvement, providing preliminary experimental and clinical data to support this hypothesis.